Detection of Expansin Proteins and Activity during Tomato Fruit Ontogeny - Rose, Jocelyn K.C. (American Society of Plant Physiologists, 2000)
Expansins are plant proteins that have the capacity to induce extension in isolated cell walls and are thought to mediate pH-dependent cell expansion. J.K.C. Rose, H.H. Lee, and A.B. Bennett ([1997] Proc Natl Acad Sci USA 94: 5955–5960) reported the identification of an expansin gene (LeExp1) that is specifically expressed in ripening tomato (Lycopersicon esculentum) fruit where cell wall disassembly, but not cell expansion, is prominent. Expansin expression during fruit ontogeny was examined using antibodies raised to recombinant LeExp1 or a cell elongation-related expansin from cucumber (CsExp1). The LeExp1 antiserum detected expansins in extracts from ripe, but not preripe tomato fruit, in agreement with the pattern of LeExp1 mRNA accumulation. In contrast, antibodies to CsExp1 cross-reacted with expansins in early fruit development and the onset of ripening, but not at a later ripening stage. These data suggest that ripening-related and expansion-related expansin proteins have distinct antigenic epitopes despite overall high sequence identity. Expansin proteins were detected in a range of fruit species and showed considerable variation in abundance; however, appreciable levels of expansin were not present in fruit of the rin or Nr tomato mutants that exhibit delayed and reduced softening. LeExp1 protein accumulation was ethylene-regulated and matched the previously described expression of mRNA, suggesting that expression is not regulated at the level of translation. We report the first detection of expansin activity in several stages of fruit development and while characteristic creep activity was detected in young and developing tomato fruit and in ripe pear, avocado, and pepper, creep activity in ripe tomato showed qualitative differences, suggesting both hydrolytic and expansin activities.